2011
DOI: 10.1021/jf202060p
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Glucomannan and Inulin Systematically Modulate Antioxidant Defense in Rats Fed a High-Fat Fiber-free Diet

Abstract: The aim of this study was to investigate the effects of konjac glucomannan (KGM) and inulin on the balance between pro-oxidative status and antioxidative defense systems in the colon, liver, and plasma of rats fed a high-fat fiber-free diet. Male Sprague-Dawley rats (n = 8 animals per group) were fed a high-fat (25% corn oil, w/w) fiber-free diet or that supplemented with KGM or inulin fiber (5%, w/w) for 4 weeks. The index of pro-oxidative status, malondialdehyde (MDA), and blood lymphocyte DNA damage; the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
4
30
1
Order By: Relevance
“…In addition, Erhardt et al [58] investigated the effect of different dietary compositions on the in vitro oxygen radical production in human feces and found that a diet rich in fiber diminishes the in vitro formation of reactive oxygen species in human feces and decreases MDA levels in plasma. Wu and Chen [59] have shown that the supplementation of inulin to a high-fat and fiber-free diet led to an increase in the antioxidant defense system by up-regulating gene expression of glutathione peroxidase and catalase in colon mucosa as well as a reduction in MDA levels in the colon of rats. In addition to the modulation of antioxidant enzymes in colonic mucosa cells, antioxidant and MDA-lowering effects of dietary fiber could be mediated by its prebiotic properties, i.e., promoting the growth of bifidobacteria and lactobacilli [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Erhardt et al [58] investigated the effect of different dietary compositions on the in vitro oxygen radical production in human feces and found that a diet rich in fiber diminishes the in vitro formation of reactive oxygen species in human feces and decreases MDA levels in plasma. Wu and Chen [59] have shown that the supplementation of inulin to a high-fat and fiber-free diet led to an increase in the antioxidant defense system by up-regulating gene expression of glutathione peroxidase and catalase in colon mucosa as well as a reduction in MDA levels in the colon of rats. In addition to the modulation of antioxidant enzymes in colonic mucosa cells, antioxidant and MDA-lowering effects of dietary fiber could be mediated by its prebiotic properties, i.e., promoting the growth of bifidobacteria and lactobacilli [7].…”
Section: Discussionmentioning
confidence: 99%
“…It does this partly by up-regulating the gene expressions of glutathione peroxidase and catalase. In addition, butyrate promotes antioxidative status in the blood by elevating the α-tocopherol level (Wu and Chen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glucomannan (GM) is a soluble dietary fiber and nondigestible polysaccharide. Ingestion of GM stabilizes blood glucose concentrations and soluble dietary fiber is associated with decreased levels of oxidative stress [23]. Nondigestible saccharides, which escape the digestion by small intestinal enzymes, reach the large intestine and are fermented by intestinal microbes.…”
Section: Introductionmentioning
confidence: 99%